Analisis Perbandingan Kinerja Keuangan PT. Bank Rakyat Indonesia (Persero) Tbk dan PT. Campina Ice Cream Industry Tbk. Berbasis Laporan Keuangan - Isma Azis Riu (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to analyze and compare the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk, a banking company, and PT Campina Ice Cream Industry Tbk, a non-banking company, based on their financial statements for the 2023–2024 period. The analysis was conducted to determine differences in asset structure, profitability, leverage, liquidity, and earnings stability between the two companies, which are from different industrial sectors. The research method used was a quantitative descriptive approach with a financial statement analysis approach through the statement of financial position, income statement, and financial ratios. Data were obtained from the companies' annual financial reports published on the Indonesia Stock Exchange. The results show that PT Bank Rakyat Indonesia (Persero) Tbk has relatively stable financial performance with consistent profitability, maintained asset quality, and a strong capital structure. On the other hand, PT Campina Ice Cream Industry Tbk exhibits good liquidity and capital structure, but experiences a decline in profitability due to increased operating expenses and production costs. This study also found that industry characteristics influence the company's asset structure, revenue sources, and risk level. Digitalization has had a positive impact on the efficiency and business development of both companies, although its impact on profitability is more significant in the banking sector. This study concludes that banking companies have higher profit stability than non-bank manufacturing companies, which are more sensitive to changes in operating costs and market conditions.